Graduate employability among low academic achievers - Mohd Alwi, Norhayati; Isa, Khadijah; Zainal Abidin, Nor Hafizah; Yussof, Salwa Hana; Abu Bakar, Intan Suryani (Adam Marszałek Publishing House, 2020)
This study aims to provide insights on how and why a specialised training programme could help graduates with low performance to compete fairly in the job market. This study used an action research design, where a total of 12 graduates with low academic achievement were trained under a specialised training programme consisting of two phases within the period of ten months. Despite having low academic achievements in terms of Cumulative Grade Point Average (CGPA), the employability opportunities of those graduates were high as they were equipped with the highly sought after GST knowledge and certification and various important soft skills such as time management, communication, analytical skills and leadership. This study demonstrated that engaging graduates in a specially designed program that aimed to enhance their technical knowledge and soft skills coupled with some work experience is indeed a value added strategy to enhance graduates employability. This is particularly applicable to those who are low achievers as it provides them with some kind of competitive advantages. The findings suggest that despite having low CGPA, their employability opportunities, particularly in the accounting and commercial industries, were relatively high. This study provides some guidance to policymakers and educators on how universities and industries may collaborate to mitigate unemployment issues among the accounting graduates.